2020
DOI: 10.1016/j.gr.2019.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Application of LA ICP-MS analysis of arsenopyrite to gold metallogeny of the Meguma Terrane, Nova Scotia, Canada

Abstract: Investigation of gold metallogeny in the Paleozoic Meguma terrane (Canada) is conducted through LA-ICP-MS analysis of arsenopyrite collected from eight slate-belt style vein gold deposits using a novel approach integrating elemental distribution maps and their derived elemental paragenesis with multi-element binary plots. The data reveal two distinct gold events: 1) an early event characterized by a Co-Ni-Mo-Sb-Se elemental association related to initial growth of arsenopyrite that reflects the presence of inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Gourcerol (2018) reported that the Au versus Ag plot is used to track Au mineralization and hydrothermal events [43]. The hydrothermal event has up to 100 ppm Au present in the sulfides, likely as invisible Au or nanoparticles [44]. The subsequent hydrothermal events are recorded by an upgrading due to the zone refining of the early Au, with it either having a similar Au/Ag ratio or a much higher one.…”
Section: Discussionmentioning
confidence: 99%
“…Gourcerol (2018) reported that the Au versus Ag plot is used to track Au mineralization and hydrothermal events [43]. The hydrothermal event has up to 100 ppm Au present in the sulfides, likely as invisible Au or nanoparticles [44]. The subsequent hydrothermal events are recorded by an upgrading due to the zone refining of the early Au, with it either having a similar Au/Ag ratio or a much higher one.…”
Section: Discussionmentioning
confidence: 99%
“…Even if preliminary observations may not be conclusive as to the presence of Sb mineralization, reproducible concentrations of more than 10 ppm Sb in quartz are likely to signify that a vein network has very elevated potential for Sb mineralization in the immediate proximity. Much in the same way as LA-ICP-MS analyses of pyrite and arsenopyrite can help targeting potential Au deposit (e.g., Morey et al, 2008;Cook et al, 2013;Velasquez et al, 2014;Traore et al, 2016;Gourcerol et al, 2018Gourcerol et al, , 2020Zhang et al, 2020), our approach may help tracking Sb mineralization and improve prospecting during mineral exploration.…”
Section: Sb In Quartz As Vector To Mineralizationmentioning
confidence: 97%
“…In a given deposit, sulphide mineral texture and geochemical signature may thus indicate gold input and crystallisation-remobilisation stages (e.g. Velasquez et al, 2014;Fougerouse et al, 2017;Pearce et al, 2018;Gourcerol et al, 2018aGourcerol et al, , 2018bGourcerol et al, , 2020Kontak et al, 2018;Large and Maslennikov, 2020;Combes et al, 2021) and could be used as pathfinders for high-grade gold ore (e.g. Kadel-Harder et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been widely used to study sulphide trace element geochemistry within individual deposits (e.g. Large et al, 2007Large et al, , 2009Cook et al, 2013;Hazarika et al, 2013;Velasquez et al, 2014;Gourcerol et al, 2018aGourcerol et al, , 2018bGourcerol et al, , 2020Augustin and Gaboury, 2019;Li et al, 2019;Wu et al, 2019a;Kadel-Harder et al, 2020;Combes et al, 2021). When coupled to the microstructural and -textural characterisation of ore-bearing mineral assemblages, such geochemical datasets allow to reassess ore genetic models (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation